Pengaruh Lama Pengempaan dan Konsentrasi Bahan Perekat Alami Serbuk Cangkang Kepiting Terhadap Sifat Papan Partikel Mahoni - , FAJAR HARI WINARTO, Agus Ngadianto, S.Hut., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The wood processing in Indonesia still produces waste in massive amount that includes sawing powder, slabs and wood pieces. The multiple types of wood wastes found in Indonesia have not been taken into advantages maximally of the types is the mahogany wastes resulted from the sawing industry. The production of a particle board is an effort to turn the wood waste into a product that has higher economic values. The board production in the industry scale usually implements the formaldehyde syntetic adhesive which has dangerous risk for the human health due to the produced emission. The search for the other alternative material as the natural adhesive material for the wood composite adhesive that is more renewable and eco-friendly becomes a specific challenge for the industry of wood composite